Utilization of Audio Visuals in Increasing Students' Interest in Learning in Pancasila Education Subjects at SMP Negeri 12 Palu - Sukmawati, Sukmawati; Alanur, Shofia Nurun; Jamaludin, Jamaludin; Rahmadan, Sri; Sinta, Preti; Kawadi, Julistri A; Marwah, Marwah; Nurwahida, Nurwahida; Anggun, Anggun; L, Nurmala; Yulitayani, Sri; Muharrama, Muharrama; Feni, Feni (CV. Rayyan Dwi Bharata, 2025)
This research aims to examine the effectiveness of using audio-visual media through animated videos at SMP Negeri 12 Palu in increasing students' interest in learning Pancasila education. The results show that the application of media such as video, animation, images and sound has succeeded in increasing interest in learning, understanding of the material, student participation, as well as critical and collaborative thinking skills. Audio visual media presents learning material in an interesting and interactive way, superior to conventional methods, because it is able to stimulate more senses. These findings emphasize the importance of audio-visual media in creating a comprehensive and motivating learning process for students. This research is a type of qualitative research with a descriptive approach which is a series of activities to obtain data that is as it is without being in certain conditions.